2022
DOI: 10.3390/reprodmed3010003
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation Endometrial Transcriptomics in Natural Conception Cycle of the Rhesus Monkey

Abstract: There is no report on preimplantation phase endometrial transcriptomics in natural conception cycles of primates. In the present study, the whole-genome expression array of endometrium on Days 2, 4, and 6 post-ovulation (pov) in proven natural conception (Group 1; n = 12) and non-mated, ovulatory (Group 2; n = 12) cycles of rhesus monkeys was examined, compared, and validated. Of fifteen (15) genes showing differential expression (>2-fold; pFDR < 0.05), six genes (CHRND, FOXD3, GJD4, MAPK8IP3, MKS1, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
(184 reference statements)
0
1
0
Order By: Relevance
“…Further, there is a notion that post-ovulatory sexual activity may help facilitate a successful implantation and pregnancy, suggesting an adaptive role for this reproductive behaviour. Reports have demonstrated that semen facilitates the endometrial receptivity towards embryo growth and implantation [7][8][9] .…”
Section: Main Textmentioning
confidence: 99%
“…Further, there is a notion that post-ovulatory sexual activity may help facilitate a successful implantation and pregnancy, suggesting an adaptive role for this reproductive behaviour. Reports have demonstrated that semen facilitates the endometrial receptivity towards embryo growth and implantation [7][8][9] .…”
Section: Main Textmentioning
confidence: 99%